CTD profile measurements from a glacier-fed fjord conducted close to a sensor deployment site during cruise TU19 (Nuup Kangerlua, Greenland) - Beaton, Alexander; Hendry, Katharine R; Hatton, Jade Elizabeth; Meire, Lorenz (PANGAEA, 2025)
This dataset contains temperature conductivity, turbidity and depth measurements from a CTD profile taken in a glacier-fed fjord (Nuup Kangerlua, Greenland). The profile was conducted in the vicinity of a sensor mooring that contained nitrate, dissolved silica and CTD sensors.